Peran dan Tanggung Jawab Dayah Dalam Membina Akhlak Santri - Jailani Jailani (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Dayah plays a part in fostering the morality of students today. The goals is to create and develop the personality of Muslims who have personality of faith and piety to God, and also good morality and benefit to the community. Dayah is as one of the non-formal Islamic educational institutions that play a role in founding students morality by inculcating moral values through the learning process of Islamic religious discipline.